Distribution of Vibrio vulnificus and Other Lactose-Fermenting Vibrios in the Marine Environment - Oliver, James D. (1983)
During the summer of 1981, 3,887 sucrose-negative vibrios were isolated from seawater, sediment, plankton, and animal samples taken from 80 sites from Miami, Fla., to Portland, Maine. Of these, 4.2% were able to ferment lactose. The lactose-positive strains isolated from the various samples correlated positively with pH and turbidity of the water, vibrios in the sediment and oysters, and total bacterial counts in oysters. Negative correlations were obtained for water salinity. Numerical taxonomy was performed on 95 of the lactose-fermenting environmental isolates and 23 reference strains. Five clusters resulted, with the major cluster containing 33 of the environmental isolates and all of the Vibrio vulnificus reference strains. The 33 isolates, which produced an acid reaction in lactose broth within hours of initial inoculation, represented 20% of all lactose-fermenting vibrios studied. These isolates were nearly identical phenotypically to clinical strains of V. vulnificus studied by the Centers for Disease Control, Atlanta, Ga., and by our laboratory, and their identification was confirmed by DNA-DNA hybridization studies. V. vulnificus was isolated from all sample types and from Miami to Cape Cod, Mass., and comparison of the environmental parameters of the eight subsites yielding this species with those of all 80 subsites revealed no significant differences. The majority of the isolates were obtained from animals, with clams providing most (84%) of these. On injection into mice, 82% of the V. vulnificus isolates resulted in death. Members of the remaining four clusters contained strains which differed from V. vulnificus in such phenotypic traits as luminescence and in urease or H(2)S production. None of the other reference cultures, including nine other Vibrio species, were contained in the remaining clusters, and these isolates could not be identified. Most of these were also lethal for mice. Phenotypic differences, potential pathogenicity, and geographic distribution of the five clusters were examined. It is concluded that V. vulnificus is a ubiquitous organism, both geographically and in a variety of environmental sources, although it occurs in relatively low numbers. The public health significance of this organism and of the other unidentified lactose-fermenting Vibrio species is discussed.